Socialization of Earthquake Disaster Mitigation to Elementary School Students Through Pocket Books - Siti Nurjanah (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract. The implementation of this Community Service (PkM) activity aims to increase the understanding of elementary school students on the attitudes that must be carried out before, during, and after the earthquake disaster. Through this PkM activity, students are expected to be able to, 1) have basic knowledge about the steps in responding to disasters properly and correctly; 2) students have an understanding of the attitude that must be done in the event of a disaster; and 3) students have an understanding of attitudes that must be done after a disaster occurs. The training participants were 30 students of SD MIN 1 Ambon. The materials presented at the time of socialization were 1) things to be prepared before a disaster occurred, 2) strategies to be implemented during a disaster, and 3) strategies to be implemented after a disaster occurred. This PkM activity was carried out through lecture methods, and demonstrations using the disaster response pocket book. The results of the training obtained are 1) students gain basic knowledge about earthquake disaster mitigation before a disaster occurs, 2) students have an understanding of attitudes that must be taken when a disaster occurs, and 3) students have an understanding of what to do after a disaster occurs. Referring to the results of this PkM activity, the school should participate more actively in carrying out socialization activities so that students have more knowledge and understanding of earthquake disaster mitigation. Keywords: mitigation, earthquake, students